Semantic decoupling: reducing the impact of requirement changes - Navarro, Israel; Leveson, Nancy; Lunqvist, Kristina (Requirements engineering, 2010)
The continuous stream of requirements changes that often takes place during software development and can create major problems in the development process. This paper defines a concept we call semantic coupling that can be used during all the phases of a system specification and design to reduce the impact of changing requirements. Within the general framework of the intent specifications, traceability matrices representing the mappings between different abstraction levels are used to evaluate the sensitivity of a given design to requirement changes. The practicality of using the approach on real software is demonstrated using the specification of the control software for a NASA robot designed to service the heat-resistant tiles on the Space Shuttle.